2019
DOI: 10.1001/jamapsychiatry.2019.1702
|View full text |Cite
|
Sign up to set email alerts
|

Association With Hospitalization and All-Cause Discontinuation Among Patients With Schizophrenia on Clozapine vs Other Oral Second-Generation Antipsychotics

Abstract: IMPORTANCE Recent meta-analyses of randomized clinical trials (RCTs) comparing clozapine with nonclozapine second-generation antipsychotics (NC-SGAs) in schizophrenia have challenged clozapine's superiority in treatment-resistant patients. However, patients in RCTs are not necessarily generalizable to those in clinical practice. OBJECTIVE To conduct a systematic review and meta-analysis to compare various outcomes of clozapine vs oral NC-SGAs in cohort studies. DATA SOURCES Systematic literature search in PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(100 citation statements)
references
References 71 publications
6
91
0
3
Order By: Relevance
“…These results have been replicated with claims data in the United States, which found a 22% reduction in the risk of hospitalization during periods following clozapine initiation (HR = 0.78, 95% CI = 0.69-0.88) (22). Similarly, a meta-analysis of cohort studies comparing clozapine treatment to non-clozapine second-generation antipsychotics found greater symptom reduction for clozapine (Hedges g, 0.22, 95% CI = 0.01-0.43), as well as lower hospitalization risk (relative risk [RR] = 0.82, 95% CI = 0.73-0.92) and all-cause discontinuation (RR = 0.73,95% CI = 0.64-0.84) (26). In addition to reductions in hospitalization, data from a cohort of 2370 individuals with TRS showed that individuals receiving clozapine treatment had almost half the mortality rate than individuals not receiving clozapine (HR = 1.88, 95% CI = 1.16-3.05) (27).…”
Section: Clozapine Eligibilitymentioning
confidence: 99%
“…These results have been replicated with claims data in the United States, which found a 22% reduction in the risk of hospitalization during periods following clozapine initiation (HR = 0.78, 95% CI = 0.69-0.88) (22). Similarly, a meta-analysis of cohort studies comparing clozapine treatment to non-clozapine second-generation antipsychotics found greater symptom reduction for clozapine (Hedges g, 0.22, 95% CI = 0.01-0.43), as well as lower hospitalization risk (relative risk [RR] = 0.82, 95% CI = 0.73-0.92) and all-cause discontinuation (RR = 0.73,95% CI = 0.64-0.84) (26). In addition to reductions in hospitalization, data from a cohort of 2370 individuals with TRS showed that individuals receiving clozapine treatment had almost half the mortality rate than individuals not receiving clozapine (HR = 1.88, 95% CI = 1.16-3.05) (27).…”
Section: Clozapine Eligibilitymentioning
confidence: 99%
“…Nev-ertheless, our study represents the largest study on a broad variety of clinically highly relevant outcomes among a severely-ill cohort of patients treated with clozapine. Furthermore, our study contributes to the discussion of clozapine's cardiovascular safety [66] with regard to its efficacy in terms of a risk-benefit evaluation. Given the presumed shared underlying neurobiology of schizophrenia and nicotine use [67][68][69], our smoking clozapine patients might define an ultra-treatment-resistant subgroup with an early onset of the disease requiring further research.…”
Section: Discussionmentioning
confidence: 92%
“…Clozapine is one of the antipsychotics most strongly associated with weight gain, hyperglycemia, and hyperlipidemia [208,209]. In a systematic review of cohort studies, clozapine was also associated with higher cardiometabolic-related risk outcomes [128]. As described before, clozapine is associated with longer survival [114]; it appears that its positive effects may outweigh its metabolic risks.…”
Section: Other Potentially Lethal Clozapine Adrsmentioning
confidence: 91%
“…If one takes a more comprehensive view of what is important in clinical practice [126], and considers effectiveness based on two systematic reviews of naturalistic cohort studies [127,128], clozapine was superior to other antipsychotics in decreasing discontinuation and decreasing hospitalization.…”
Section: Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation